THE INFLUENCE OF PLUS, MINUS AND INTERESTING (PMI) STRATEGY TOWARDS STUDENTS’ SPEAKING ABILITY IN AN INDONESIAN PRIVATE SECONDARY SCHOOL - Nikijuluw, Renata C.G.V; Puspitasari, Dewi (Universitas Negeri Makassar, 2018)
Nowadays, the lack of opportunity for students to practice speaking in English classroom makes them difficult to improve their speaking ability. Therefore, this study will address PMI, stands for Plus, Minus and Interesting strategy that can encourage students to speak by thinking the plus, minus and interesting points of the topic. This study used Quasi-Experimental research for the students at second grade of SMP-IT As-Salam Ambon. It is aimed to find out whether the students who are taught by using PMI strategy had better achievement in their speaking ability rather than those who are taught by using Question and Answer strategy. This study was conducted during 8 meetings. First meeting was the pre-test, 6 meetings were the treatment and the last meeting was the post-test. The result reveal that after PMI strategy had been applied, the students in experimental class was significantly had better achievement in speaking ability than the students in control class based on their pre-test and post-test result. Thus, PMI strategy could influence students’ speaking ability because it can open the opportunity for the students to elaborate their ideas, to help them make a decision in a short time and to increase their participation in speaking activity.